Entrepreneurship, Public Policy, and Cities - Lerner, Josh (World Bank, Washington, DC, 2014)
Since the 2008-09 global financial crises, interest among policy makers in promoting innovative, ventures has exploded. The emerging great hubs of entrepreneurial activity, like Bangalore, Dubai, Shanghai, Silicon Valley, Singapore, and Tel Aviv, bear the unmistakable stamp of the public sector. Enlightened government intervention played a key role in each region's emergence. But for each effective government intervention, dozens, even hundreds, disappointed, with substantial public spending bearing no fruit. This paper sheds light on how governments can avoid mistakes in stimulating entrepreneurship. In recent decades, efforts have increased to provide the world's poorest with financing and other assistance to facilitate their entry into entrepreneurship or the growth of their small ventures. These are typically subsistence businesses offering services like snack preparation or clothing repair. Such businesses typically allow business owners and their families to get by, but little else. The public policy literature, along with academic studies of new ventures, often does not distinguish among the types of businesses being studied. The author will focus here exclusively on high-potential new ventures and the policies that enhance them. This choice, not intended to diminish the importance of efforts to boost microenterprises, reflects the complexity of the field: the dynamics and issues involving micro firms are quite different from those of their high-potential counterparts. A substantial literature suggests that promising entrepreneurial firms can have a powerful effect in transforming industries and promoting innovation.